Comparative Analysis of Hot and Cold Brews from Single-Estate Teas (Camellia sinensis) Grown across Europe: An Emerging Specialty Product - Patricia Carloni; Alfonso Albacete; Purificación A. Martínez-Melgarejo; Federico Girolametti; Cristina Truzzi; Elisabetta Damiani (MDPI AG, 2023)
Tea is grown around the world under extremely diverse geographic and climatic conditions, namely, in China, India, the Far East and Africa. However, recently, growing tea also appears to be feasible in many regions of Europe, from where high-quality, chemical-free, organic, single-estate teas have been obtained. Hence, the aim of this study was to characterize the health-promoting properties in terms of the antioxidant capacity of traditional hot brews as well as cold brews of black, green and white teas produced across the European territory using a panel of antioxidant assays. Total polyphenol/flavonoid contents and metal chelating activity were also determined. For differentiating the characteristics of the different tea brews, ultraviolet-visible (UV-Vis) spectroscopy and ultra-high performance liquid chromatography coupled with high-resolution mass spectrometry were employed. Overall, our findings demonstrate for the first time that teas grown in Europe are good quality teas that are endowed with levels of health-promoting polyphenols and flavonoids and that have an antioxidant capacity similar to those grown in other parts of the world. This research is a vital contribution to the characterization of European teas, providing essential and important information for both European tea growers and consumers, and could be of guidance and support for the selection of teas grown in the old continent, along with having the best brewing conditions for maximizing the health benefits of tea.